Exploring into the Prehistory and Early History of Philippine Public Administration: Three Models of Weberian Administrative State in Focus - Nolasco, Liberty Ibanez (Philippine Journal of Public Administration, 2017)
Is there a Philippine Public Administration (PPA)? Since the 1980s, this big question has received few responses construing the evolution of PPA in outward-looking terms of Westernization: the early communalism (500,000 years ago), the political fragmentation (15th century), the Spanish colonial administration (1521-1898), or the intellectualized PPA (1952). Such highlights the issue of trade-off between conventionalism and empirical verifiability of PPA identity-building. In registering affirmation of the big question, the study attempts to show that when the outward-looking perspective is relaxed, the issue of trade-off is eased and the structural representations of PPA underlying even its praxis can be examined across time. This claim is tested using three models of Weberian bureaucracy, which mainly build on the works of Weber (1999), Nystrom and Nystrom (1998), and Pawlik (2010). The study yields evidence pointing to the existence of structural features and praxis of PPA 900,000 to 1,000 years ago and in the 10th century.
Keywords: Philippine Public Administration, administrative state, Weberian bureaucracy